Analysis of Financial Performance of Cigarette Companies Listed on the Indonesia Stock Exchange for the 2018-2022 Period - Sumarni. S; R, Baso; Asriadhi, Sandy (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
This study aims to analyze the financial performance of the cigarette company PT. Gudang Garam Tbk, PT. Hanjaya Mandala Sampoerna Tbk, PT. Indonesian Tobacco Tbk, PT. Bentoel Internasional Investama Tbk, and PT. Wismilak Inti Makmur Tbk which is listed on the Indonesia Stock Exchange in 2018-2022. Using quantitative descriptive methods. Theresults of the study show that PT. Hanjaya Mandala Sampoerna Tbk and PT. Wismilak Inti Makmur Tbk has high liquidity, while PT. Gudang Garam Tbk has a high current ratio but a low quick ratio. Based on the solvency analysis of PT. Gudang Garam Tbk and PT. Wismilak Inti Makmur Tbk has a good performance, while PT. Hanjaya Mandala Sampoerna Tbk, PT. Bontoel Internasional Investama Tbk, and PT. Indonesian Tobacco Tbk tends to have a high debt ratio. PT. Hanjaya Mandala Sampoerna Tbk has efficiency in the use of assets and fast inventory turnover in contrast to PT. Bontoel Internasional Investama Tbk highlighted the rapid inventory turnover but has not been efficient in the use of assets. Meanwhile, PT. Gudang Garam Tbk, PT. Indonesian Tobacco Tbk, PT. Wismilak Inti Makmur showed poor performance of activities. Judging from profitability, it shows that the ROA and ROE of cigarette companies have not reached optimal levels or are in poor condition